EFA6 controls Arf1 and Arf6 activation through a negative feedback loop - Padovani, Dominique (National Academy of Sciences, 2014)
Guanine nucleotide exchange factors (GEFs) of the exchange factor for Arf6 (EFA6), brefeldin A-resistant Arf guanine nucleotide exchange factor (BRAG), and cytohesin subfamilies activate small GTPases of the Arf family in endocytic events. These ArfGEFs carry a pleckstrin homology (PH) domain in tandem with their catalytic Sec7 domain, which is autoinhibitory and supports a positive feedback loop in cytohesins but not in BRAGs, and has an as-yet unknown role in EFA6 regulation. In this study, we analyzed how EFA6A is regulated by its PH and C terminus (Ct) domains by reconstituting its GDP/GTP exchange activity on membranes. We found that EFA6 has a previously unappreciated high efficiency toward Arf1 on membranes and that, similar to BRAGs, its PH domain is not autoinhibitory and strongly potentiates nucleotide exchange on anionic liposomes. However, in striking contrast to both cytohesins and BRAGs, EFA6 is regulated by a negative feedback loop, which is mediated by an allosteric interaction of Arf6-GTP with the PH-Ct domain of EFA6 and monitors the activation of Arf1 and Arf6 differentially. These observations reveal that EFA6, BRAG, and cytohesins have unanticipated commonalities associated with divergent regulatory regimes. An important implication is that EFA6 and cytohesins may combine in a mixed negative-positive feedback loop. By allowing EFA6 to sustain a pool of dormant Arf6-GTP, such a circuit would fulfill the absolute requirement of cytohesins for activation by Arf-GTP before amplification of their GEF activity by their positive feedback loop.